Review on Machine Learning and Deep Learning and Its Benefit for Beef and Pork Classification - Syaukani, Imam (Journal of Multi-Disciplinary Engineering Reviews, 2025)
Machine learning and deep learning has been widely applied in wide application.  Notably, deep learning recently received considerable attention in classification.  This paper reviewed the theory regarding machine learning and deep learning and then concentrate the review on previous research that used the deep learning and machine learning technique for classification between beef and pork.  It also reviewed the hybrid method to enhanced the accuracy.